Diversity, biogeography, evolutionary relationships, and conservation of Eastern Mediterranean freshwater mussels (Bivalvia: Unionidae) - Lopes-Lima, Manuel (2018)
Located at the junction between Europe, Africa, and Asia, with distinct evolutionary origins and varied ecological and geographical settings, together with a marked history of changes in orogeny and configuration of the main river basins, turned the Eastern Mediterranean into a region of high diversity and endemism of freshwater taxa. Freshwater mussels (Bivalvia, Unionidae) from the Western Palearctic have been widely studied in their European range, but little attention has been dedicated to these taxa in the Eastern Mediterranean region and their diversity and phylogeography are still poorly understood. The present study aims to resolve the diversity, biogeography, and evolutionary relationships of the Eastern Mediterranean freshwater mussels. To that end, we performed multiple field surveys, phylogenetic analyses, and a thorough taxonomic revaluation. We reassessed the systematics of all Unionidae species in the region, including newly collected specimens across Turkey, Israel, and Iran, combining COI + 16S + 28S and COI phylogenies with molecular species delineation methods. Phylogeographical patterns were characterized based on published molecular data, newly sequenced specimens, and species distribution data, as well as ancestral range estimations. We reveal that Unionidae species richness in the Eastern Mediterranean is over 70% higher than previously assumed, counting 19 species within two subfamilies, the Unioninae (14) and Gonideinae (5). We propose two new species, Anodonta seddoni sp. nov. and Leguminaia anatolica sp. nov. Six additional taxa, Unio delicatus stat. rev., Unio eucirrus stat. rev., Unio hueti stat. rev., Unio sesirmensis stat. rev., Unio terminalis stat. rev. removed from the synonymy of Unio tigridis, as well as Unio damascensis stat. rev. removed from the synonymy of Unio crassus, are re-described. The nominal taxa Unio rothi var. komarowi O. Boettger, 1880 and Unio armeniacus Kobelt, 1911 are proposed as new synonyms of Unio bruguierianus, and Anodonta cyrea Drouët, 1881 and Anodonta cilicica Kobelt and Rolle, 1895 as new synonyms of Anodonta anatina. Also, the presence of Unio tumidus in the Maritza River is confirmed. The phylogeographic patterns described here are interpreted concerning major past geological events. Conservation needs and implications are presented, together with populations and species conservation priorities.